2011
DOI: 10.1039/c0em00542h
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, sources, and potential toxicological significance of PAHs in drinking water sources within the Pearl River Delta

Abstract: The Pearl River Delta (PRD) region is one of the most population-dense areas in China. The safety of its drinking source water is essential to human health. Polycyclic aromatic hydrocarbons (PAHs) have attracted attention from the scientific community and the general public due to their toxicity and wide distribution in the global environment. In this work, PAHs pollution levels from the drinking source water in nine main cities within the PRD were investigated. P 15 PAHs concentrations during the wet season v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
0
14
2
Order By: Relevance
“…Naphthalene and pyrene both had very similar composition. The % composition patterns found here are not very different from those reported by An et al (25) who found out that 3-ring PAHs were most dominant in most cases followed by 4-ring PAHs and 2-ring PAHs. Acenaphthene and phenanthrene are both 3-ring PAHs while naphthalene has 2-rings.…”
Section: Individual Pahscontrasting
confidence: 66%
See 2 more Smart Citations
“…Naphthalene and pyrene both had very similar composition. The % composition patterns found here are not very different from those reported by An et al (25) who found out that 3-ring PAHs were most dominant in most cases followed by 4-ring PAHs and 2-ring PAHs. Acenaphthene and phenanthrene are both 3-ring PAHs while naphthalene has 2-rings.…”
Section: Individual Pahscontrasting
confidence: 66%
“…This shows how PAH pollution is wide spread in the country as PAHs are a global pollutant (4). An et al (25) studied the distribution, sources, and potential toxicological significance of PAHs in drinking water sources within the Pearl River Delta in China. The sum of 15 PAHs studied ranged from 58.8-3159.9 ng −1 (25).…”
Section: Total Pahsmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples were analyzed using an Agilent Technologies 7890A gas chromatography coupled with a 5975C mass spectrometer detector (GC-MSD) following documented methods (An et al, 2011b;Qiao et al, 2010;Zeng et al, 2008) with slight modification. A HP-5MS silica fused capillary column (30 m  250 mm  0.25 mm) was applied for three groups of analytes in this study.…”
Section: Sample Extraction Cleanup and Analysismentioning
confidence: 99%
“…SVOCs such as PAHs and OCPs have been frequently detected in the PRD region (Guo et al 2008;An et al 2011;Feng et al 2012), whereas the small rivers in this region have not been investigated. Compared to the main river, the small rivers are more closely connected to the pollution sources and weaker in self-cleaning capacity.…”
Section: Introductionmentioning
confidence: 99%